A Materials Acceleration Platform for Organic Laser Discovery (Adv. Mater. 6/2023). Issue 6 (9th February 2023) - Wu, Tony C; Aguilar‐Granda, Andrés; Hotta, Kazuhiro; Yazdani, Sahar Alasvand; Pollice, Robert; Vestfrid, Jenya; Hao, Han; Lavigne, Cyrille; Seifrid, Martin; Angello, Nicholas; Bencheikh, Fatima; Hein, Jason E.; et al.
Abstract : Accelerated Materials Discovery In article number 2207070, Tony C Wu, Alán Aspuru‐Guzik, and co‐workers report a materials acceleration platform to automatically search for high‐performing organic laser molecules, which includes synthesis, product identification, and property measurements. This platform has discovered two state‐of‐the‐art organic lasers from searching through 40 potential candidates. The results show the potential of automated synthesis and accelerated discovery of materials.